A multicenter experience from Lebanon in childhood and adolescent acute myeloid leukemia - Farhat, Hussein Z. (2015)
Background Acute myeloid leukemia (AML) is a disease with marked heterogeneity. Despite major improvement in outcome, it remains a life-threatening malignancy. Demographic and clinical data on pediatric AML is lacking among the Lebanese population. Purpose We aimed to identify clinical, molecular and outcome data in children with AML in Lebanon. Methods A retrospective chart review of children with AML diagnosed in three Lebanese hospitals during the past 8 years was conducted. Results From May 2002 through March 2010, we identified 24 children with AML in Saint George Hospital University Medical Center, University Medical Center Rizk Hospital, and Abou-Jaoude Hospital. Males and females were equally represented; median age at diagnosis was 9 years (range 1–24) and median WBC at diagnosis was 31 × 109/L (range: 2.1–376 × 109/L). Twenty five percent of patients (6 out of 24) had acute promyelocytic leukemia (APL). Karyotype was normal in 33% of patients; t(8;21), inv (16), t(8;9), t(7;11), t(9;11), complex chromosomal abnormality, monosomy 7 and trisomy 8 were the most common cytogenetic abnormalities encountered. Patients were treated on different European and North American protocols. Twelve patients (50%) achieved morphologic CR after cycle 1, 6 of them (50%) had bone marrow relapse within 11 months from diagnosis. Nine patients underwent allogeneic stem cell transplant, and 3 of them are alive at 5 years post-transplant. Early death rate was 16.6% of patients, mainly those with APL and a presenting WBC > 10 × 109/L. Fifty per cent of APL patients had an early death due to DIC despite starting ATRA therapy. Overall, median survival for AML patients who died from disease progression was 25.8 months (range: 1–60 months). Overall disease-free survival was 30.4%. Patients < 10 years of age had a 50% survival rate compared to 0% in patients > 10 years. Conclusions Our report highlights the needs in Lebanon for better supportive care of children with APL, including faster ATRA administration and, aggressive transfusions, easy access to stem cell transplant for high-risk AML patients and the need for a national homogenous treatment strategy for children with AML.